Bacillus tropicus YJ33 and Medicago sativa L. Synergistically Enhance Soil Aggregate Stability in Saline–Alkali Environments - Jingjing Li; Yajuan Che; Shiyang Chen; Mengge Liu; Mengmeng Diao; Chao Yang; Wenke Jia (Microorganisms)
Soil salinization represents a significant global environmental challenge, necessitating the urgent amelioration of saline–alkali lands. As a critical functional component of the soil system, soil aggregates play a pivotal role in enhancing soil structure and are essential for nutrient cycling and plant growth. However, the synergistic effects of plants and microorganisms on alterations in soil aggregate composition, stability, and nutrient content in saline–alkali soils remain inadequately understood. In this study, three saline soil gradients from the Yellow River Delta were analyzed: low saline soil (S1, 1.65 g/kg), medium saline soil (S2, 4.54 g/kg), and high saline soil (S3, 6.57 g/kg). For each gradient, four experimental treatments were established: (1) inoculation of Bacillus tropicus YJ33 alone (B), (2) planting of alfalfa alone (M), (3) combined alfalfa cultivation with B. tropicus YJ33 inoculation (MB), and (4) an unamended control (CK). These treatments were implemented in controlled laboratory pot experiments to evaluate the individual and synergistic impacts of alfalfa and B. tropicus YJ33 on saline soil aggregate stability and structural organization. Overall, B. tropicus YJ33 inoculation significantly promoted the growth and nutritional quality of alfalfa. B, M, and MB treatment increased the contents of total carbon (TC), total nitrogen (TN), and available phosphorus (AP) and promoted the activities of soil alkaline phosphatase (S-ALP) and soil urease (S-UE) in the soil. Simultaneously, these treatments resulted in a reduction in the proportion of micro-aggregates, an increase in the proportion of large and small aggregates, and significantly enhanced mean weight diameter (MWD) and geometric mean diameter (GMD), improving the stability of soil aggregates. Random forest analysis identified AP, B. tropicus YJ33, salinity, TC, and available nitrogen (AN) as key determinants of alfalfa biomass. Partial least squares (PLS) modeling further corroborated the role of B. tropicus YJ33 in enhancing soil nutrient content, improving aggregate stability, and increasing alfalfa yield. In conclusion, B. tropicus YJ33 was demonstrated to enhance the stability of soil aggregates and nutrient availability in saline–alkali soils, thereby significantly promoting the growth, yield, and nutritional quality of alfalfa.